2013
DOI: 10.1093/humrep/det424
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency may be a risk factor for recurrent pregnancy losses by increasing cellular immunity and autoimmunity

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
188
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(205 citation statements)
references
References 71 publications
6
188
2
9
Order By: Relevance
“…In a retrospective cross sectional study of 133 women diagnosed with recurrent pregnancy loss, Ota et al [21] reported that 63 out of 133 women (47.4 %) had hypovitaminosis D (less than 30 ng/ml) and that NK cell levels and NK cytotoxicity at effector to target cell (E:T) ratio of 25:1 were significantly higher in the low vitamin D group when compared with subjects with normal vitamin D levels. In addition, in vitro NK cytotoxicity assays demonstrated significant suppression at an E:T ratio of 50:1 when treated with Vitamin D compared to the control group, demonstrating evidence that low Vitamin D may be associated with increased NK cell activity in women with recurrent pregnancy loss.…”
Section: Pregnancy Lossmentioning
confidence: 99%
“…In a retrospective cross sectional study of 133 women diagnosed with recurrent pregnancy loss, Ota et al [21] reported that 63 out of 133 women (47.4 %) had hypovitaminosis D (less than 30 ng/ml) and that NK cell levels and NK cytotoxicity at effector to target cell (E:T) ratio of 25:1 were significantly higher in the low vitamin D group when compared with subjects with normal vitamin D levels. In addition, in vitro NK cytotoxicity assays demonstrated significant suppression at an E:T ratio of 50:1 when treated with Vitamin D compared to the control group, demonstrating evidence that low Vitamin D may be associated with increased NK cell activity in women with recurrent pregnancy loss.…”
Section: Pregnancy Lossmentioning
confidence: 99%
“…In women with RPL, decreased vitamin D level was associated with the increased prevalence of antiphospholipid antibody, antinuclear antigen antibody, anti-ssDNA, and anti-thyroperoxidase antibody. In addition, peripheral blood CD19 + B and CD56 + NK-cell levels and NK cytotoxicity were significantly higher in women with low vitamin D level when compared with those of normal vitamin D level [6]. Normal pregnancy is associated with Th2 shift in T-cell immunity [7].…”
mentioning
confidence: 95%
“…In addition, vitamin D deficiency is a predisposing factor for various female diseases such as osteoporosis, uterine fibroids, endometriosis, and breast cancer and a risk factor for obstetrical complications such as gestational diabetes and preeclampsia [4,5]. Recently, we have reported that 47.4% of women with recurrent pregnancy losses (RPL) have vitamin D deficiency [6]. In women with RPL, decreased vitamin D level was associated with the increased prevalence of antiphospholipid antibody, antinuclear antigen antibody, anti-ssDNA, and anti-thyroperoxidase antibody.…”
mentioning
confidence: 99%
“…Além disso, as mulheres grávidas com baixos níveis séricos de 25[OH]D podem apresentar maior risco de vaginose bacteriana, mas não a parto por cesariana 42,45 . Estudo conduzido por Ota et al (2014), mostrou que as mulheres com baixo nível de VD aumentaram significativamente as probabilidades de anormalidades autoimunes, que é um fator de risco para falência reprodutiva. A citotoxicidade das células NK e a polarização Th1 foram significativamente reduzidas in vitro pela VD, e a secreção e a polarização reduzidas da VD em células NK.…”
Section: Desfechos Materno-fetaisunclassified
“…Portanto, esses resultados levantam a possibilidade de que a VD possa estar disponível como uma nova opção terapêutica para falhas reprodutivas. É necessário um estudo mais aprofundado para elucidar o papel imuno-regulador da VD e se a administração suplementar de VD pode prevenir o aparecimento da perda de gravidez 47 . As concentrações de VD estão associadas ao peso ao nascer 37 56 .…”
Section: Desfechos Materno-fetaisunclassified